IMPLEMENTASI MANAJMEN MUTU LAYANAN KHUSUS DALAM ME INGKATKAN DAYA SAING SEKOLAH - Moh. Khaidir (UNISAN JURNAL, 2024)
Good service quality performance is expected to meet consumer expectations and if these expectations are met then community satisfaction can be fulfilled both in the aspects of physical evidence, reliability, responsiveness, empathy and guarantee which are indicators of service quality at SMA Negeri 3 Prabumulih. The approach used in this research is qualitative research with a descriptive type of analysis. Data from each dimension of service quality in this research was collected through interview, observation and documentation techniques. The research data were analyzed using triangulation techniques. The results of the research prove that: (1) The quality of service is a physical (tangible) evidence aspect of the availability of facilities and infrastructure that support learning, but library facilities, UKS rooms and prayer rooms are not yet available. SMA Negeri 3 Prabumulih continues to provide health services and reading room facilities by utilizing unused classrooms. Meanwhile, to overcome the lack of prayer rooms by implementing prayer practices in the classroom. (2) The quality of service in the empathy aspect is demonstrated by concern for service users, in this case students, attention to students who have below average ability levels. (3) The quality of service aspect of reliability is providing services that are in accordance with what was promised, every information submitted is accurate and on target. (4) The quality of service in the responsiveness aspect of SMA Negeri 3 Prabumulih is demonstrated by the willingness and ability to help with difficulties faced by students and respond quickly to any input, both criticism and suggestions. (5) The quality of service aspect of assurance (assurance) creates trust and provides assurance to customers that the level of success of the learning process at SMA Negeri 3 Prabumulih and the output is quite satisfactory. Adequate teacher competency based on education and staffing levels. The guarantees provided include the number of graduates reaching one hundred percent, the number of graduates accepted into state secondary schools and outstanding academic abilities.